Load management in a distributed multimedia streaming environment using a fault-tolerant hierarchical system - Aybay, Hadi Isik; Shah, Mohammad Ahmed (Tubitak Scientific & Technological Research Council Turkey, 2015)
In contrast to text-only forms of communications, multimedia uses a combination of audiovisual means alongside textual modes of communication. Streaming multimedia is such multimedia that is constantly delivered by a provider of the multimedia to a client. In streaming multimedia the streamed content is continually presented to and received by the end user. Distributed multimedia systems (DMSs) deliver multimedia content to end-users by means of distributed multimedia databases and distributed information servers. These DMSs are designed to deliver multimedia content over a network. A fault-tolerant redundant hierarchy (Red-HI)-based load management policy for a distributed multimedia streaming system is proposed in this paper. The main objectives of this policy are to provide fault tolerance while increasing the flexibility offered in the network by improving network resource utilization. Another advantage of this policy is that it provides popularity-zone centric dynamic multimedia object placement. The load management and fault tolerance are achieved using Red-HI for the multimedia servers coupled with parent-only query flooding policy. We show through simulations that our scheme outperforms the traditional pure hierarchy employed in most distributed multimedia systems.
Keywords: End-to-end performance; quality of service; load balancing; fault tolerance; redundant hierarchy; distributed multimedia streaming; dynamic object placement; video-on-demand